Les contacts parent-enfant suite au placement en famille substitut : liens avec la stabilité du placement - Karine Poitras; George M. Tarabulsy (Enfances, Familles, Générations, 2017)
Research Framework : Preschool children are less likely to be reunified to their biological parents after being in foster care and generally have more stable foster placement. However, little is known about the factors associated with stable placement in preschool children and, in particular, the role of parent-child contact on placement trajectories of these children. Objectives : This study examines the relation between parent-child contacts after foster placement and three aspects related to foster placement stability : the prospect of parent-child reunification, the occurrence of family reunification failure, and the number of placement changes experienced by the child. Methodology : Fifty-four biological parents and 43 foster parents responsible for young children aged between 12 and 43 months were met. Socio-demographic and contact arrangements information were collected during individual interviews and biological parents’ commitment to their child placed in a foster home was measured. Results : Results show that parent-child contact is positively and significantly or marginally associated with prognosis for family reunification, even after controlling for potentially confounding ecological characteristics. Beyond contact arrangements, biological parental commitment to their child is associated with the prospect of family reunification. Conclusions : Thus, results of this study confirm the role of parental commitment following foster care and support the development of interventions that promote this component of parenthood. Contribution : This study sheds light on the distinct roles of parental commitment and parent-child contact on the prospect of family reunification and supports future research in this area.